Three essays on cross-border syndicated loans: evidence from developing countries - Wang, Xiaotian (2022)
Nowadays, a key policy issue facing the monetary and financial regulation authorities is the impact of cross-border capital flows. The global financial crisis has highlighted the role of financial integration and development worldwide in triggering financial distress and instability. Strengthened regulation of cross-border banking behaviours, which usually bear pro-cyclical nature and generate risks, has become necessary for governments to fend off domestic and global financial stability in the age of an integrated world economy. Compared with FDI and equity financing, credit flows are less favourable to efficient risk sharing and more prone to destabilizing, thus they deserve more regulatory attention. Given academic and policy attention attached to cross-border syndicated loans is relatively insufficient in contrast with the significance of such financing channels in the global market, my thesis aims to fill the gap and study the determinants and impact of cross-border syndicated loans, one of the main components of cross-border capital flows. Research on the issue could help policy makers to keep better track of gross cross-border capital flows, enhance global coordination over financial regulation, and help businesses and banks to better understand potential risks and consequences when choosing SLs as a financing method.